Trimetazidine - Assessment of Therapeutic Effects for liver damage in rats - Vijay H. Mate; Vijaya A. Pandit (International Journal of Pharma and Bio Sciences, 2020)
Incidence of drug-induced hepatotoxicity is increasing day by day. Many traditional medicines including indigenous sources and herbal preparations are developed for effective hepatoprotective action. However,this study was planned to explore the effect of therapeutic administration of antianginal drug, Trimetazidine, in CCl4, induced liver damage in albino rats.Carbon tetrachloride (0.5 ml/kg, i.p. once daily for 7 days) was used to induce hepatotoxicity. Liver damage was assessed by change in liver function tests (SGOT, SGPT, ALP, proteins, and bilirubin). Pentobarbitone sleeping time and histological examination of the liver were also done. Trimetazidine (doses 5 and 10 mg/kg p. o.) was administered after the development of liver damage. Liv.52® was used as Positive Control. Data wereanalyzed by one way ANOVA, followed by Dunnett’s test.CCl4 induced elevation of serum SGOT, SGPT, ALP, and bilirubin (total and direct) and reduction in protein level. Trimetazidine, in both the doses, significantly prevented these findings of liver damage. Consistent results were also shown by pentobarbitone sleeping time and histological examination of the liver. The results were comparable to the positive control, Liv.52®. The therapeutic administration of Trimetazidine shows hepatoprotective activity against CCl4 induced liver damage.